Effects of polymerization degree on recovery behavior of PVA/PVP hydrogels as potential articular cartilage prosthesis after fatigue test - Y. Shi; D. S. Xiong; Y. Peng; N. Wang (eXPRESS Polymer Letters)
Poly (vinyl alcohol)/poly (vinyl pyrrolidone) (PVA/PVP) hydrogels with various polymerization degrees of PVA were synthesized by a repeated freezing-thawing method. The influence of polymerization degree on microstructure, water content, friction coefficient, compressive fatigue and recovery properties of PVA/PVP hydrogels were investigated. The results showed that higher polymerization degree resulted in larger compressive modulus and lower friction coefficient. The fatigue behaviors of PVA/PVP hydrogels were evaluated under sinusoidal compressive loading from 200 to 800 N at 5 Hz for up to 50 000 cycles. The unconfined uniaxial compressive tests of PVA/PVP hydrogels were performed before and after fatigue test. During the fatigue test, the height of the hydrogel rapidly decreased at first and gradually became stable with loading cycles. The compressive tangent modulus measured 0 h after fatigue was significantly larger than the values obtained before test, and then the modulus recovered to its original level for 48 h after test. However, the geometry of hydrogels could not return to the original level due to the creep effects. PVA/PVP hydrogels prepared with lower polymerization degree showed better recovery capability than that prepared with high polymerization degree.